LEXICAL BUNDLES IN STUDENTS’ ESSAY WRITING - Nadia Ulfa; Kismullah Abdul Muthalib (Universitas Syiah Kuala, 2020)
This study was aimed to find out the frequency of three- word and four- word of lexical bundles which were used in the essay writing of the undergraduate students studying at English Education Department of Syiah Kuala University. This study employed a corpus based analysis which compiled a specialized small corpus consisting of 161 students’ essays under linguistic topic. In order to generate the frequent list of sequences, computational software named AntConc 3.5.8 by Laurent Anthony was used. The results showed that the number of three-word bundles was higher than four-word bundles in terms of the frequency of co-occurrence in which the most common expression the function of as three-word bundles and the advantages of being as four-word bundles were found.